2021
DOI: 10.11594/ijmaber.02.02.03
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-Experimental Research on the Implementation of Selected Class-room Assessment Techniques for Music, Arts, Physical Education, and Health

Abstract: The primary objective of this study is to examine and identify the classroom assessment techniques (CATs) that might provide and help teachers through assessment and evaluation processes in Music, Arts, Physical Education, and Health (MAPEH) using pre-experimental research through one-group pretest-posttest design. The study was conducted at Jose Abad Santos High School in Manila, Philippines during the third grading period of the researcher’s practicum. The sample of the study consists of 20 students selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…In other words, the average score of students in the posttest is greater than that of students in the pretest. In line with previous research, this is indicated by the intervention that makes a difference in the pretest and posttest scores (Tabuena, 2021). These findings indicate that inquiry-based learning or setting fosters students' ability to interpret, analyze, conclude, evaluate, explain and self-regulate, which are critical thinking skills (Wale & Bishaw, 2020).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, the average score of students in the posttest is greater than that of students in the pretest. In line with previous research, this is indicated by the intervention that makes a difference in the pretest and posttest scores (Tabuena, 2021). These findings indicate that inquiry-based learning or setting fosters students' ability to interpret, analyze, conclude, evaluate, explain and self-regulate, which are critical thinking skills (Wale & Bishaw, 2020).…”
Section: Resultssupporting
confidence: 88%
“…In addition, significant differences were also found in the posttest in favor of the experimental group regarding astronomical achievement and interest in astronomy (Önal & Onal, 2021). In line with previous research, these results can also be used to help understand the best way of learning and, as an alternative, in learning that does not go well (Tabuena, 2021). This implementation can provide innovations by providing problems and solutions, especially in students' understanding of concepts.…”
Section: Resultssupporting
confidence: 74%
“…A pre-experimental research design was used in this study (Creswell & Creswell, 2017;Ramadhana & Allo, 2021;Tabuena, 2021). A single group pretest and posttest design was used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies raised concerns about assessing students' PE, especially on neutrality-related problems (Brennan, 1992;Freeman, 2015;Judith, 1990). Research (Tabuena, 2021) states that few PE teachers, regardless of academic discipline, are aware and knowledgeable of the important considerations in constructing an appropriate assessment process. Lack of knowledge about the characteristics of various appropriate and good evaluative measures in the assessment is also an obstacle.…”
Section: Dinda Arisetya Purwadi Yulingga Nanda Hanief Ulma Erdilanitamentioning
confidence: 99%
“…Lack of knowledge about the characteristics of various appropriate and good evaluative measures in the assessment is also an obstacle. (Tabuena, 2021) explains that Classroom evaluation is an advanced continuous feedback technique with particular consequences for teaching and learning. Effective teaching is a systematic process that uses the analysis and interpretation of data gathered via specific procedures to provide advice for the teaching process.…”
Section: Dinda Arisetya Purwadi Yulingga Nanda Hanief Ulma Erdilanitamentioning
confidence: 99%